Pros and Cons of using Artificial Intelligence in Accounting: The Dual effect and Financial Control - Altawalbeh, Mohammad A.; Al Frijat, Yaser S.; Alhajaya, Mohammad E. (International Review of Management and Marketing, 2025)
This paper investigates the opportunities and threats of using Artificial intelligence in accounting by surveying a sample of 300 Jordanian accounting professionals. The results confirm that AI enhances the accuracy, productivity, cost control, and levels of fraud identification by automating routine tasks, therefore improving the decision-making processes. On the other hand, there are also challenges to adopting AI, including high costs of implementation, training requirements due to expertise required, data protection issues, and ethical issues involving transparency and reliability. Responding to these challenges necessitates strategic investments in training programs and the creation of ethical frameworks that will ensure responsible and secure application of AI. The results give actionable suggestions through which policymakers, accountants, and developers of technology will use the benefits of AI through mitigations of its challenges. Further studies will need to involve wider populations and longer-term research to make a more profound statement on the transformation of AI within global accounting practices.